The growing economy - Meade, J. E. (London: G. Allen & Unwin, 1968)
The book attempts to discuss the theory of economic growth with a minimum of mathematical analysis. The author constructed model to study the process of equilibrium growth i.e. steady-state growth. In fact, the model is designed to show the way in which the simplest form of classical economic system would behave during a process of equilibrium growth. This model provides the relation to increase the income and population. It analyses the influence of income, capital, labour and technology on development. It also gives the conditions under which the growth of economy is possible. He tries to establish a relationship between population growth and income growth.
Includes index
Being vol 2 of A principles of political economy.
rpm 22/06/2017
Loans
Keywords: Economics; Economic conditions; Growing economy